Facile Synthesis of Mesoporous Graphene Materials from Potassium Humate for Supercapacitor Electrodes. (24th July 2018) - Huang, Guangxu; Geng, Qianhao; Kang, Weiwei; Liu, Yingbin; Duan, Bin; Zhang, Chuanxiang
Abstract : Mesoporous graphene materials (MG-X) were prepared from potassium humate coupled with magnesium acetate. The freeze-drying pretreatment and MgO particles not only prevent the agglomeration of graphene sheets and form mesopores but also help to reduce the oxygen content and enlarge the sp 2 carbon domain of MG-X. MG-X possess optimized characteristics including large specific surface area (>1100 m 2 ·g −1 ), high mesoporosity ( 90%), and low oxygen content ( 7%). When used as supercapacitor electrodes, MG-X demonstrate optimal electrochemical performances among all materials prepared here, such as high gravimetric capacitance (150 F·g −1 at high current density of 3.3 A·g −1 ) and enhanced rate capability with the capacitance retention of 80% from 0.041 to 3.3 A·g −1 . Moreover, MG-5 exhibits good cycling stability with a capacitance retention of 98.6% after 1000 cycles at 2.46 A·g −1 . This work provides a facile and efficient preparation method for mesoporous graphene materials used as supercapacitor electrodes.